Mecanismo para personalização da privacidade em dispositivos móveis - Melo, Leonardo Leite de (Universidade Federal de São Carlos, 2013)
Technological advances present in mobile devices feature such as camera, GPS tracking system, internet connection which has enabled the installation of applications that use these resources enabling access to almost unlimited amount of information. Some users have on their mobile devices more sensitive data than those contained on their personal computers, generating a growing concern about the possibility that such information can be used maliciously, resulting in damages for theft of information or physical vulnerability. This dissertation proposes a tool that allows to transfer for the user of mobile devices the control of access permission, as well as aims to make user to be aware of what each application is running. This tool can be used by an individual or by companies to manage security devices of their employees. A prototype implementation of the mechanism for customization of privacy on mobile devices using the Android platform as well as the use and performance assessments conducted in order to validate the proposal are presented in this dissertation.
Keywords: Privacidade e personalização; Android (Recurso eletrônico); Controle de acesso; Sistemas de segurança; Access control; Security; Privacy and personalization; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO